Gendered Conceptions of Preconception Health: A Thematic Analysis of Men's and Women's Beliefs about Responsibility for Preconception Health Behavior. Issue 5 (3rd May 2020) - Mello, Susan; Stifano, Sara; Tan, Andy Sl; Sanders-Jackson, Ashley; Bigman, Cabral A.
Abstract : Preconception health (PCH) focuses on taking steps before a pregnancy to safeguard the health of the woman and future baby. Although recommendations to improve PCH target all people of reproductive age, research shows most interventions and messages focus primarily on women, which may contribute to existing normative beliefs that women are more responsible for protecting children's health. In this study, we explore society's gendered expectations of responsibility for engaging in recommended PCH behaviors (i.e., avoiding smoking, drinking, and environmental toxins). An applied thematic analysis of online survey responses from U.S. men and women (N = 573) identified five main themes and related subthemes: body and health, shared responsibility, choice and moral obligation, gender stereotypes, and doubt and uncertainty. Both men and women frequently referenced biological connections between prospective parents and offspring as justification for PCH behaviors. When challenging PCH recommendations, respondents mentioned excessive control of women and men's secondary role in reproduction. Overall, gender stereotypes were more commonly expressed in relation to men yet reflected both traditional and contemporary male roles (i.e., as supporters, co-parents). When judging personal responsibility, women commonly viewed PCH behaviors as the 'duty of a good mother'. Implications for PCH communication research and practice are discussed.